S3M - A Suggestion Mechanism for Semantic Web Service Composition - Silva, Diogo P. Busanello da; Weber, Mathias H.; Siqueira, Frank (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2015: Proceedings of the 21st Brazilian Symposium on Multimedia and the Web, 2015)
Web Service composition is a complex and error-prone process that requires the support of software tools in order to become feasible. Composition tools can help a developer to select compatible services from vast service repositories, taking into account characteristics such as port compatibility, availability, cost, and so on. This paper describes S3M, a service suggestion mechanism that, coupled with the CVFlow workflow editor, helps developers to select services and to build compositions. Service suggestions are given to the user taking into account the semantic description of Web Services in SAWSDL format.